Rotational isomerization of small carboxylic acids isolated in argon matrices: Tunnelling and quantum yields for the photoinduced processes - Maçôas, Ermelinda M. S. (2005)
The quantum yields for internal rotation around the C–O bond induced by excitation of the first overtone of the hydroxyl stretching mode in formic, acetic, and propionic acids isolated in solid Ar are comparatively discussed. The tunnelling kinetics for isomerization from the higher energy arrangement of the carboxylic group (cis) to the lower energy arrangement (trans) in this series of compounds is also analysed. Finally, the quantum yield for the Cα–C isomerization in propionic acid was investigated and, in contrast with the C–O isomerization, shown to be probably sensitive to the local matrix morphology.